The Analysis of the Bankruptey Potential Comparative by Altman Z-Score, Springate and Zmijewski Methods at Cement Companies Listed in Indonesia Stock Exchange - Januri Januri, S.E., M.M., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The Analysis of the Bankruptey Potential Comparative by Altman Z-Score, Springate and Zmijewski Methods at Cement Companies Listed in Indonesia Stock Exchange